On the Problem of Possibilistic-Probabilistic Optimization with Constraints on Possibility/Probability - Yazenin, Alexander; Soldatenko, Ilia (Fuzzy Logic and Applications, 2019)
The problem of possibilistic-probabilistic linear programming with constraints on possibility and probability is investigated. For the case of normally distributed random parameters of the model and under the most general assumptions concerning the properties of probability distributions, its equivalent determinate analogue is constructed which is the quadratic programming model.